Specific changes and clinical significance of plasma D-dimer during pregnancy and puerperium: a prospective study - Qin Xu; Li Dai; Hong-Qin Chen; Wei Xia; Qi-Lin Wang; Cai-Rong Zhu; Rong Zhou (BMC, 2023)
Abstract Background Pregnant and puerperal women are high-risk populations for developing venous thromboembolism (VTE). Plasma D-dimer (D-D) is of good value in the diagnosis of exclusion of VTE in the nonpregnant population. Since there is no consensus reference range of plasma D-D applicable to pregnant and puerperal women, the application of plasma D-D is limited. To investigate the change characteristics and the reference range of plasma D-D levels during pregnancy and puerperium and to explore the pregnancy- and childbirth-related factors affecting plasma D-D levels and the diagnostic efficacy of plasma D-D for excluding VTE during early puerperium after caesarean section. Methods A prospective cohort study was conducted with 514 pregnant and puerperal women (cohort 1), and 29 puerperal women developed VTE 24-48 h after caesarean section (cohort 2). In cohort 1, the effects of the pregnancy- and childbirth-related factors on the plasma D-D levels were analyzed by comparing the differences in plasma D-D levels between different groups and between different subgroups. The 95th percentiles were calculated to establish the unilateral upper limits of the plasma D-D levels. The plasma D-D levels at 24-48 h postpartum were compared between normal singleton pregnant and puerperal women in cohort 2 and women from the cesarean section subgroup in cohort 1, binary logistic analysis was used to analyze the relevance between plasma D-D level and the risk of VTE developing 24-48 h after caesarean section, and a receiver operating characteristic (ROC) curve was used to assess the diagnostic efficacy of plasma D-D for excluding VTE during early puerperium after caesarean section. Results The 95% reference ranges of plasma D-D levels in the normal singleton pregnancy group were ≤ 1.01 mg/L in the first trimester, ≤ 3.17 mg/L in the second trimester, ≤ 5.35 mg/L in the third trimester, ≤ 5.47 mg/L at 24-48 h postpartum, and ≤ 0.66 mg/L at 42 days postpartum. The plasma D-D levels of the normal twin pregnancy group were significantly higher than those of the normal singleton pregnancy group during pregnancy (P < 0.05), the plasma D-D levels of the GDM group in the third trimester were significantly higher than those of the normal singleton pregnancy group (P < 0.05). The plasma D-D levels of the advanced age subgroup at 24-48 h postpartum were significantly higher than those of the nonadvanced age subgroup (P < 0.05), and the plasma D-D levels of the caesarean section subgroup at 24-48 h postpartum were significantly higher than those of the vaginal delivery subgroup (P < 0.05). The plasma D-D level was significantly correlated with the risk of VTE developing at 24-48 h after caesarean section (OR = 2.252, 95% CI: 1.611-3.149). The optimal cut-off value of plasma D-D for the diagnosis of exclusion of VTE during early puerperium after caesarean section was 3.24 mg/L. The negative predictive value for the diagnosis of exclusion of VTE was 96.1%, and the area under the curve (AUC) was 0.816, P < 0.001. Conclusions The thresholds of plasma D-D levels in normal singleton pregnancy and parturient women were higher than those of nonpregnant women. Plasma D-D had good value in the diagnosis of exclusion of VTE occurring during early puerperium after caesarean section. Further studies are needed to validate these reference ranges and assess the effects of pregnancy- and childbirth-related factors on plasma D-D levels and the diagnostic efficacy of plasma D-D for excluding VTE during pregnancy and puerperium.